REFORMING THE INTERNATIONAL COURT OF JUSTICE: THE URGENCY FOR A MORE ADVANCED SCOPE OF JURISDICTION - Novena Clementine Naomi (Padjadjaran Journal of International Law, 2020)
Abstract It can be argued that in facing the paramount problems of the twenty first century, one of the core elements of establishing a world with friendly relation among States is by the constitution of a healthy judicial field considering the fact that disputes among States are in no way can be avoided. For more than seven decades the International Court of Justice has served the world and the Member States of the United Nations in particular with judicial service as it bears the function as the principal judicial organ of the United Nations. However, by analyzing the development of international law, while the ICJ has contributed to improving the relation between States by way of providing States with the proper settlement of disputes, the current system—mostly designed at a time of different global challenges and priorities—seems to have exceeded its capacity to be nimble and responsive to the needs of today’s world. This article seeks to offer recommendations on how to optimize the Court’s function by means of reforming its contentious jurisdiction. The purpose of this article is to open more possibilities to optimize the Court, by making the Court’s jurisdiction mandatory and compulsory to all States and offer a possibility of expansion of jurisdiction as to include ratione materiae jurisdiction. Keywords: Jurisdiction, International Court of Justice, Reform Abstrak Dapat dikatakan bahwa dalam menghadapi masalah terpenting di abad dua puluh satu, salah satu unsur utama dalam menciptakan dunia dengan hubungan baik antar negaranya adalah melalui terciptanya ranah peradilan yang sehat, menimbang sengketa antar negara yang merupakan sebuah keniscayaan. Selama lebih dari tujuh dekade, Mahkamah Internasional telah melayani dunia dan negara anggota dari Perserikatan Bangsa-Bangsa terkhusus dalam hal penyediaan pelayanan peradilan terkait dengan fungsinya sebagai organ peradilan utama Perserikatan Bangsa-Bangsa. Bagaimanapun, dengan menganalisa perkembangan hukum internasional, walaupun Mahkamah Internasional telah berkontribusi dalam meningkatkan hubungan baik antar negara dengan cara menyediakan cara penyelesaian sengketa yang memadai, sistem yang ada sekarang ini—sebagian besar dirancang pada masa dengan tantangan dan prioritas global yang berbeda—tampaknya telah tidak efektif dalam menanggapi kebutuhan dunia zaman ini. Tulisan ini bertujuan menawarkan rekomendasi-rekomendasi perihal optimalisasi dari fungsi Mahkamah Internasional dengan cara reformasi yurisdiksi kasus kontensius yaitu diantaranya dengan menjadikan yurisdiksi Mahkamah sebagai wajib bagi setiap negara anggota, serta memperluas jangkauan yurisdiksi Mahkamah berdasarkan prinsip ratione materiae. Kata Kunci: Mahkamah Internasional, Reformasi, Yurisdiksi